(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Lymphadenopathy in the head and neck region is a common clinical issue with diverse causes, ranging from benign conditions to malignancies. Fine Needle Aspiration Cytology (FNAC) has become an essential diagnostic tool due to its minimally invasive nature, cost-effectiveness, and ability to provide rapid, accurate diagnoses. FNAC is particularly valuable for distinguishing between benign and malignant lymph node lesions and identifying specific infections like tuberculosis. Objective: This study focuses on analyzing the frequency and types of lymph node lesions in the head and neck region using FNAC. Methodology: This prospective study, conducted from January 2022 to January 2023 in the Department of Pathology at the Medical College for Women & Hospital, included a total of 53 patients. The study focused on patients presenting with head and neck swelling. Results: Chronic nonspecific lymphadenitis was the most frequently observed pathological condition of the lymph nodes, comprising 50.9% of cases. Granulomatous lymphadenitis, including both tuberculous and non-tuberculous forms, was identified in 33.9% of cases, with the tuberculous form being more common. Acute suppurative lymphadenitis accounted for 13.2% of cases, while metastatic lesions, squamous cell carcinoma was the least common, each representing 1.9% of the total cases. The most common age group affected was 11 to 20 years (32.0%), and females were more frequently affected (71.7%). Conclusion: This study reveals that chronic nonspecific lymphadenitis is the most frequently encountered lymph node condition, followed by granulomatous lymphadenitis, particularly of tuberculous origin, acute suppurative lymphadenitis, and metastatic involvement either squamous cell carcinoma or adenocarcinoma. Frequently female were frequently affected and most common age group in between 11-20 years. FNAC is recommended as a safe, reliable minimally invasive method for diagnosing head and neck lesions. It serves as a complementary diagnostic procedure to histopathological examination in the diagnosis and management of palpable head and neck lesions. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):58-62